Utilisation Of Sawdust In Cyclone Gasifier For Electrical Generation. - Miskam, M.A.; Idroas, M.Y.; Alauddin, Z.A.Z.; Mustafa, K.F.

(untitled)
A great amount of sawdust produce everyday from sawmills and wood-based industries. Sawdust generally considered as a number industry waste can seriously after the environment and becomes a potential health problem.